Attitudes and practices of exercise among pregnant mothers in Singapore - Yin Ru Tan; Kok Hian Tan; Fei Dai; Hak Koon Tan; Lay Kok Tan (Singapore Medical Journal)
Introduction: There is increasing evidence demonstrating the safety and benefits of physical activity (PA) in uncomplicated pregnancies. Literature has shown that pregnant women around the world do not engage in adequate exercise. This study aims to assess the current practices of exercise among pregnant women in Singapore, determine the proportion of women meeting different PA targets and evaluate the factors influencing the practice of exercise. Methods: In this cross-sectional study, pregnant women in different trimesters of pregnancy from KK Women’s and Children’s Hospital and Singapore General Hospital were surveyed. Information regarding patient demographics, attitudes and perceptions of exercise, and practice of exercise was collected. The International Physical Activity Questionnaire (IPAQ) was used to determine the amount of PA. Results: A total of 201 pregnant women aged 20–44 years were surveyed. Almost all (99.0%) participants thought that exercise was beneficial in pregnancy. Only 31.6% of them engaged in any moderate or vigorous leisure-time PA (LTPA) and they were active for a median of 120 min/week. Only 12.6% of the pregnant women met the national recommendations of at least 150 min of moderate exercise per week. The amount of total PA performed was lower among women in later trimesters of pregnancy and higher among working mothers. Conclusion: Although most Singaporean pregnant women perceived exercise as beneficial, the majority did not engage in PA. Most of the participants did not meet the international PA targets and recently published national guidelines. More can be done to promote the uptake of exercise in pregnancy and optimise metabolic management of pregnant women in Singapore.